The context of Prabumulih Market Snacks as a support in learning probability material - Sakiman, Novi Komariyatiningsih; Indra Putri, Ratu Ilma; Zulkardi, Zulkardi; Susanti, Ely; Hartono, Yusuf; Nusantara, Duano Sapta (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to produce learning activities that can help students understand the concept of probability material using the PMRI approach through Prabumulih City market snacks. This research was conducted at SMAN 6 Prabumulih, class 12. The research method used was design research with validation research type (preparation stage and pilot experiment). The instruments used in this research were observation, documentation, interviews and tests. This research produces student learning estimates (HLT) in the form of student learning trajectories in probability material. The researcher tested the sequence of activities and conjectures of students' thinking that had been designed at the preparation stage on 8 students and compared the results obtained. This testing was carried out at the design experiment stage, namely a pilot experiment to produce learning trajectories in the form of appropriate learning activities on probability material, the subject of enumeration rules. The results of data analysis conclude that the resulting learning activities can be seen as an alternative method for teachers to help students learn the concept of opportunity. The context of market snacks that researchers use are relevant to probability material and improve the reasoning ability of students